Exponential Dichotomy of the Two-Dimensional Linear Differential System - Ni Hua; Wang Jing; Bai Min (Journal of Mathematics)
This paper deals with a class of two-dimensional linear differential systems with periodic coefficients. A sufficient condition for the exponential dichotomy of the linear system is given by the fixed point theorem and variable substitution, and some new results are obtained.